Al-Āmil wa Aśaruhu fī Tafsīr wa Ta’qīd al-Nahwi Al-‘Arabī - Yahya, Dahiru (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
The term “Amil” refers to the grammatical factor that that determines the inflectional ending of a word. Classical and Modern Scholars of Arabic Grammar discuss on its important to the understanding the text, supporting or criticizing. This article aims to study the “Amil” and its positive or negative impact on Arabic grammar, by presenting scholars’ opinions, analyze them, and draw conclusions, using a descriptive and analytical approach. The study revealed that; the concept of “Amil” underwent a distortion after Khalil and his student Sibawayh, as it was seen as a building element and a connector of sentence structure elements, whereas others saw it as a bringer of grammatical signs. The reason some grammarians deviate from classicals’ concept of “Amil” was their influence by philosophical and other religious sciences, such as jurisprudence and theology. The theory emerged with Abdullah ibn Abi Ishaq, then passed through Isa ibn Umar, and flourished with Khalil and Matured with Sibawayh. The differences among grammarians in the theory of “Amil” reflect their intellectual orientations, with each influenced by their own school of thought.